Outbreaks Associated with Untreated Recreational Water — United States, 2000–2014. Issue 8 (30th July 2018) - Graciaa, Daniel S.; Cope, Jennifer R.; Roberts, Virginia A.; Cikesh, Bryanna L.; Kahler, Amy M.; Vigar, Marissa; Hilborn, Elizabeth D.; Wade, Timothy J.; Backer, Lorraine C.; Montgomery, Susan P.; Evan Secor, W.; Hill, Vincent R.; et al.
Abstract : This report summarizes trends in outbreaks associated with untreated recreational water exposure from 2000–2014; this includes infections with pathogens of concern for transplant recipients, such as norovirus, Shigella, and Cryptosporidium .